Purification and partial characterization of a novel lectin from Ruta montana roots - Messai, Alima; Necib, Youcef (Journal of Phytology, 2022)
Lectins are proteins or glycoproteins, which participate in various biological processes. The purpose of this study was to purify new lectin from Ruta montana roots. Lectin of Ruta montana has been purified from roots using ultrafiltration and precipitation with ammonium sulfate followed by gel filtration chromatography whereas protein estimation was done by Bradford’s method. Within sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS–PAGE) analysis, the extract exhibited three bands and one band after purification. The molecular weight of lectin was determined by SDS–PAGE and gel filtration chromatography, which was found to be a monomeric protein of approximately 28.8 kDa. The agglutination activity of Ruta montana lectins was stable within a temperature range from 4 to 50° C for 30 min and the pH range from 4.2 to 9. This study presents a natural source of lectins that can be used in several other studies due to its different biological activities.